The role and principles of tourist zoning in Bulgaria - O. V. Gorbunova; A. N. Mikhailin (Управление)
The article describes the experience with tourist zoning in Bulgaria - main principles and goals of the tourism zoning into separate tourist regions. The tourist regions and their main indicators have been analyzed. The Concept was approved in 2015 and plays a key role in the development of the Bulgarian tourist product on the international market and the popularization of the country as an all-year round tourist destination. Currently the tourist zoning occupied the entire territory of the country and consists of nine regions: Danube Region, Balkan Mountains Region, Rose Valley Region, Thracian Region, Rhodope Region, Rila-Pirin Region, Sofia Region, Northern Seaside Region, Southern Seaside Region. Each of the above regions has its own specialization and uniqueness, which allows for a more effective regional marketing and makes each region more recognizable. The article summarizes the system of management of the regions and the government’s support in the creation of organizations which participate in the management of the tourist regions. A comparative analysis of the tourist zoning has been made in comparison with other EU countries like Ireland, Croatia, and Romania. The result of the analysis shows that the other countries also have regions with disproportionate allocation of territory and level of development of tourist development. As a conclusion, a well-developed tourist zoning is an effective instrument for the development of the tourism potential and the diversification of the tourist product taking into account the needs of the international markets. The tourist zoning experience can be used by Russia in the development of a marketing plan for the international market for tourist services.